2009
DOI: 10.1007/s11096-009-9287-y
|View full text |Cite
|
Sign up to set email alerts
|

Drug-related problems identified in medication reviews by Australian pharmacists

Abstract: These data illustrate the prevalence of drug-related problems and the ability of pharmacists to identify these problems in the Australian models of medication review. The nature and frequency of problems varied between reviews for home-dwelling and care-facility patients. Such information may be used to better focus the training of practitioners based on the most frequently encountered health problems and the nature of common drug-related problems in the two settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
87
5
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(117 citation statements)
references
References 18 publications
8
87
5
6
Order By: Relevance
“…14) In addition, pharmacists can become more eŠectively involved by reviewing medication histories and oŠering interviews and counseling to patients' families and caregivers. 12) EŠects of pharmacist involvement, such as identiˆ-cation of drug interactions and duplicate therapies, 15) time delays prior to rehospitalization, 16) and reductions in drug-related problems, 17) have been demonstrated following medication reviews conducted during visits to patients' homes. In addition, comprehensive assessment combining medication reviews with interviews and counseling has been reported to improve patients' understanding of their medications.…”
Section: Introductionmentioning
confidence: 99%
“…14) In addition, pharmacists can become more eŠectively involved by reviewing medication histories and oŠering interviews and counseling to patients' families and caregivers. 12) EŠects of pharmacist involvement, such as identiˆ-cation of drug interactions and duplicate therapies, 15) time delays prior to rehospitalization, 16) and reductions in drug-related problems, 17) have been demonstrated following medication reviews conducted during visits to patients' homes. In addition, comprehensive assessment combining medication reviews with interviews and counseling has been reported to improve patients' understanding of their medications.…”
Section: Introductionmentioning
confidence: 99%
“…Das MM ist das wichtigste Element zur Erhöhung der AMTS und Therapietreue. Es umfasst einige wesentliche Faktoren, die über die im Berufsalltag übliche Patientenbetreuung hinausgehen und mit denen nachweislich eine höhere Anzahl arzneimittelbezogener Probleme (ABP) erkannt und gelöst werden konnten [18,19]. Diese Faktoren sind: ein systematisches, also standardisiertes und strukturiertes Vorgehen [20,21], intensive persönliche Gespräche mit dem Patienten [22], die systematische Erfassung und Analyse aller AM [23] sowie eine Kooperation von Arzt und Apotheker im Rahmen der Patientenbetreuung [24].…”
unclassified
“…MedsChecks, Diabetes MedsChecks and Clinical Interventions by pharmacists), none of which is supported by any evidence in the context of the Australian healthcare setting. Conversely, there is evidence on the value of HMRs to consumers, 2,5,6 a demonstration of cost savings of up to $550 per HMR to the health system, 7-10 and a demonstrable track record that clearly illustrates the delivery of a truly collaborative service between GPs, patients, independent accredited pharmacists and other community or hospitalbased pharmacists [11][12][13][14][15][16][17][18] (Fig. 1).…”
mentioning
confidence: 99%
“…Australian studies have demonstrated that HMRs can resolve, manage or reduce medicine-related problems for a wide range of patients. [11][12][13][14][15][16][17][18][19][20][21] In addition, HMRs improve health outcomes; for example, in patients receiving betablockers for heart failure, an HMR resulted in a 45% reduction in likelihood of hospitalisation for heart failure at any time. 18 Another study found that an HMR in patients taking warfarin resulted in a 79% reduced likelihood of bleeding-associated hospitalisation 2-6 months after the HMR.…”
mentioning
confidence: 99%
See 1 more Smart Citation